Hubungan Antara Simtom Depresi Dengan Kecenderungan Perilaku Bunuh Diri Pada Pasien Gangguan Jiwa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Abstract: Background: generally to got the description about the correlation between depression symptom and willingness to comitted suicide behavior in mentally illness patient. Specially the purpose of this study was described about depression symptom, depression's level, willingness to comitted suicide, correlation between depression symptom and willingness to committed suicide, correlation bedween depression's level and willingness to comitted suicide, the factors that correlate with depression dan the factors that correlate with willingness to comitted suicide behavior in mentally illness patient in Grhasia Hospital, Yogyakarta. Method: this was non-experimental study, descriptive analitic correlation, with cross sectional design. The variables of this study were depression symptom and willingness to comitted suicide behavior. The instruments of this study were using Beck Depression Inventory (BDI) and comitted suicide scale. Data was collected by documentation study and questionaire. Data was analized by univariat analysis for descriptive variabel analyzing and test for dare normality, bevariate analysis for spread analyzing and correlation test between variables, data was analized by SPSS for Windows version 10.05. Results and conclusion: there was a middle correlation's level between depression symptom and willingness to comitted suicide behavior, the level of significancy was p = 0,013 and the correlation value was r = 0,238, and there was a middle correlation's level between depression level and willingness to comitted suicide behavior, the level of significancy was p = 0,003 and the correlation value was r = 0,264. Another results showed depression symptom in mentally illness patient majority was on mild scor, level of depression in mentally illness patient majority was on mild level of depression, the willingness to comitted suicide behaviour in mentally illness patient majority was on middle risk, there was a positive correlation between sex and the willingness to comitted suicide behavior and there was negative correlation between fungtional status and the willingness to comitted suicide behaviour in mentally illness patient and there was not any correlation between respondent's characteristics and level of depression in metally illness patient in Grhasia Hospital, Yogyakarta. Keywords: depression symptom, and willingness to comitted suicide behavior, mentally illness